Law and Morality: An Apparent Contradiction: Array - Gheorghiță, Nelu (Acta Universitatis Danubius. Juridica, 2021)
The issue of the connection between law and morality has been a constant concern of philosophers and jurists. The theories that develop this theme vary from a direction in which law is identified with morality, to the point where the law is being denied any influence of the morality. Although we observe that there are similarities and differences between law and morality, still the legal norms that govern the human activity in the society and that can be imposed at a given time by the public force makes the object of the legal science that has very close relations with the morality